Circulating circERBB2 as a potential prognostic biomarker for gastric cancer: An investigative study. Issue 11 (19th September 2020) - Nanishi, Kenji; Konishi, Hirotaka; Shoda, Katsutoshi; Arita, Tomohiro; Kosuga, Toshiyuki; Komatsu, Shuhei; Shiozaki, Atsushi; Kubota, Takeshi; Fujiwara, Hitoshi; Okamoto, Kazuma; Ichikawa, Daisuke; Otsuji, Eigo
Abstract: Circular RNA is a novel endogenous non‐coding RNA that can serve as a biomarker because of its stable loop structure. We investigated and examined the utility of plasma circERBB2 as a prognostic biomarker in 70 patients with gastric cancer who underwent gastrectomy. We investigated by real‐time quantitative PCR the circERBB2 concentrations in the preoperative and postoperative plasma and the circERBB2 expression in the resected tumors. The relationships between circERBB2 concentration in plasma and the clinicopathological features and prognosis were analyzed. circERBB2 was detected in the preoperative plasma samples of 37 patients. The presence of circERBB2 in preoperative plasma (high group) was significantly correlated with lymph node metastasis ( P  = .035) and tended to be correlated with men ( P  = .069). Both relapse‐free and overall survival were significantly poor in the high group ( P  = .001 and P  = .009, respectively). The Cox proportional‐hazard model revealed that the high group was an independent prognostic factor of relapse‐free survival ( P  = .038). Among 16 patients of the high group, 13 patients did not show circERBB2 in the postoperative plasma. The concentration of circERBB2 in plasma was significantly higher in patients with recurrent cancer than those recurrence‐free patients ( P  < .001). In 2 patients with recurrent cancer, plasma circERBB2 concentrations were increased, whereas, in 2 recurrence‐free patients, these concentrations hardly changed during the treatment progress. The circERBB2 concentrations in preoperative plasma samples can be considered as a noninvasive prognostic biomarker for gastric cancer. Furthermore, monitoring the postoperative plasma circERBB2 concentrations may be useful for detecting gastric cancer recurrences. Abstract : In patients with gastric cancer, high levels of preoperative plasma circERBB2 showed poor prognosis and the plasma level of circERBB2 increased at recurrence. Plasma circERBB2 can be a noninvasive prognostic biomarker and useful for the detection of gastric cancer recurrences.